Dynamics of cardiovascular parameters in combined aortic malformations under the influence of a physical therapy program during the rehabilitation process - Serhii Kalmykov; Iuliia Kalmykova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study hemodynamic parameters and the reaction of the cardiovascular system to the dosed physical load of patients combined aortic defect with heart failure of the I degree under the influence of the complex physical therapy program developed by us during the rehabilitation process. Material & Methods: the study involved 26 middle-aged men with a diagnosis: combined aortic valve disease, HF I st. Result: dynamics of functional parameters of the cardiovascular system of patients under the influence of the physical therapy program is analyzed. Conclusion: the combination of morning hygienic gymnastics, therapeutic gymnastics, independent activities and dosed walking with a therapeutic massage contributes to the normalization of vascular tone, motor-vascular reflexes and blood pressure, increasing the tolerance of the cardiovascular system to physical activity.